Audit Committee and the Overall Performance of Companies - R. Regin; S. Suman Rajest; Shynu T; Steffi. R (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The impact of audit committees and boards of directors on company performance is investigated. primarily the number of members on the board and their ability to make decisions without outside influence, as well as the audit committee's composition, authority, expertise, and frequency of meetings. Although agency theory predicts that a more impartial board leads to greater results, this paper discusses resource dependency theory, which holds that non-independent directors can improve a company's performance. Accounting scandals and other worldwide corporate governance failures have had a significant impact on stakeholders and economies at all levels during the past few decades. But we couldn't find any correlation between audit committee qualities and financial outcomes in our analysis. The foregoing results provide light on the inner workings of corporate governance.